Composition of intestinal microbial communities in the small intestine of rats before and after T. gondii infection. - Ji-Xin Zhao (22056386) (2025)
(A–B) Bar plots showing taxonomic composition at the phylum and species levels across groups before and after infection. (C) Box plots depicting the relative abundance of major bacterial phyla, including Bacillota, Actinomycetota, Pseudomonadota, Bacteroidota, and Verrucomicrobiota, at different infection stages. (D) Box plots illustrating changes in the relative abundance of representative bacterial species, including Lactobacillus johnsonii, Limosilactobacillus reuteri, Lactobacillus intestinalis, Rothia nasimurium, and Streptococcus salivarius, following T. gondii infection. Statistical significance was determined using the Wilcoxon rank-sum test: *P < 0.05; **P < 0.01.